KEMAMPUAN UKURAN PERUSAHAAN MEMODERASI PENGARUH LEVERAGE PADA AUDIT DELAY - Pravita, Karina; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
The time span between the date of the financial statements issued after audited by an independent auditor who passes the final limit of accuracy with the expiry date of the publication financial statements in accordance with Bapepam-Financial Statements. Audit delay is measured quantitatively in the number of days between the date of the closing of the company until the date of signing of the audited statements. This study aimed to determine the size of the company as a moderating influence on audit delay leverage. The population in this research is manufacturing companies listed in Indonesia Stock Exchange 2013-2015 period. The samples used as many as 101 companies with a purposive sampling technique. The analysis technique used is Moderated Regression Analysis (MRA). The analysis showed that the size of the company's moderate leverage effect on audit delay which weakens the influence exerted leverage on audit delay.
Keywords: audit delay, leverage, company size